Study on the Prevalence of Depression and Anxiety among Diabetes Mellitus patients in Tertiary Care Hospital- A Prospective Cross-sectional Study. - Tamang, Pem (Asian Journal of Pharmaceutical Research and Development, 2020)
Background: Diabetes mellitus is one of the most predominant, chronic disease afflicting globally with its amplifying burden. The association of diabetes with psychological disorders exists with depression and anxiety being the most common, often remains undiagnosed or unidentified eventually leading to a decline in functional abilities and self-care, worsening the health profile of the patients and contributing to both morbidity and mortality. This study explores the association of psychiatric problems with diabetes mellitus and their related risk factors. Objectives: To investigate the association and the prevalence of psychiatric disorders (depression and anxiety) among diabetic patients and access their associated risk factors. Methods: A prospective cross-sectional study was conducted for six months in 105 diabetic patients from the outpatient department. Hospital Anxiety and Depression Scale (HADS) was used to evaluate the symptoms of anxiety and depression. Data were analyzed using Statistical Package for the Social Sciences (SPSS) version 25.0. Results: Overall 53(50.5%) were observed with the symptoms of anxiety while 45(42.9%) with symptoms of depression respectively. The prevalence of marked anxiety and depression was observed higher in a female. Anxiety and depression were also common among participants with moderate social support. Anxiety and depression were greater among patient who were illiterate (OR=1.50, 95% CI 0.92-5.38), unemployed (OR=7.50, 95% CI 1.29-43.61) with low income (PR=3.09 95% CI 0.92-10.36) and who were retired (OR=6.00, 95% CI 0.81-44.35).Conclusion: The result showed a high prevalence of depression and anxiety among female than in the male. Most of the patients developed moderate or severe anxiety and depression. Various factors such as low income, age, low education, unemployed, uncontrolled diabetes were associated with anxiety and depression. Awareness programs and health education should be conducted. Counseling and appropriate medication should be initiated to reduce future complications. Key words: